Internal Factors of Development of Psychological Readiness for Professional Activities in Cynologist Officers - Radchuk, Halyna; Afanasiev, Anatolii; Sofiian, Dmytro; Adamska, Zoriana; Perig, Iryna (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The purpose of our research is to carry out empirical study and analysis of internal factors of the development of psychological readiness for professional activities in cynologist officers. The article gives empirical evidence of internal factors of psychological readiness for professional activities in cynologist officers. The motivational and purposive, active and operational, emotional and volitional, reflexive and controlling components of psychological readiness are outlined. Three internal factors of psychological readiness of cynologist officers for professional activities are identified and analysed with the help of factor analysis of empirical indicators: awareness of psychological readiness for professional activities, a responsible subjective position, the ability to act independently, and take decisions.